Development of Career Centers of Russian Universities: Challenges and Opportunities - Margarita D, Mironova; Svetlana V, Markova; Natalya V, Ivanova; Elmira N, Khisamutdinova (Journal of Ecohumanism, 2025)
Placement training of students for employment is a serious challenge for modern Russian universities. University graduates are faced with solving the problem of employment in the face of continuous transformation of the labor market. As a result, the issue of training highly professional specialists capable of adapting to the dynamically changing requirements of employers and willing to build a successful career throughout their lives is on the agenda. As the university practice of career centers shows, the job search assistance and employment support is usually carried out within its framework. Meanwhile, the issue of training students for career development should become a key one in the philosophy of university education. In modern conditions, universities are designed to prepare a student who is potentially capable of acting independently to develop his career to meet the challenges of the labor market and his own vision of an individual educational trajectory and professional interests. Thus, university training programs for specialists in a context of ever-changing technologies in the professional sphere need to be adjusted accordingly. It assumes restructuring the system of relations between all the subjects of the educational process, when it is necessary to take into account the importance of readiness for employability and building a career of a university graduate and his life self-determination. Despite the importance of the employability problem and career development readiness to achieve the sustainable development of the Russian economy, this topic has been little studied by domestic scientists. At the same time, Russia's higher education development agenda began to see the problem of graduate employment as a special one especially during the pandemic. In particular, the topic on developing career centers of universities has gained momentum in the large-scale program of the Ministry of Science and Higher Education of the Russian Federation on the development of Russian universities Priority-2030. Thus, this study will be useful to the stakeholders of systemic changes in processes related to building employment conditions for students and graduates. Also, this study can contribute to analytical basis development for the expansion of career centers of Russian universities.